2018
DOI: 10.1001/jamaophthalmol.2017.6111
|View full text |Cite
|
Sign up to set email alerts
|

Association of Functional Loss With the Biomechanical Response of the Optic Nerve Head to Acute Transient Intraocular Pressure Elevations

Abstract: IMPORTANCE The acute biomechanical response of the optic nerve head (ONH) to intraocular pressure (IOP) elevations may serve as a biomarker for the development and progression of glaucoma. OBJECTIVE To evaluate the association between visual field loss and the biomechanical response of the ONH to acute transient IOP elevations. DESIGN, SETTING, AND PARTICIPANTS In this observational study, 91 Chinese patients (23 with primary open-angle glaucoma [POAG], 45 with primary angle-closure glaucoma, and 23 without gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…This LC depth pattern across the disease stages could be explained in part by a recent study by Tun et al [42]. Evaluating the correlation between VF indexes values and pressure-induced LC displacement, the authors found that while patients with mild glaucoma presented a posterior LC displacement, those with more advanced disease had an anterior LC displacement [4244]. These data suggest that much of the LC depth changes in glaucoma patients appear to occur in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This LC depth pattern across the disease stages could be explained in part by a recent study by Tun et al [42]. Evaluating the correlation between VF indexes values and pressure-induced LC displacement, the authors found that while patients with mild glaucoma presented a posterior LC displacement, those with more advanced disease had an anterior LC displacement [4244]. These data suggest that much of the LC depth changes in glaucoma patients appear to occur in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, when evaluating ALD values in healthy eyes and eyes with different glaucoma stages, although we found greater ALD values in eyes with mild-to-moderate glaucoma (deeper cups than controls), the same did not occur in eyes with more advanced disease, as mean ALD values seemed to decrease in these eyes. This LC depth pattern across the disease stages could be explained in part by a recent study by Tun et al [42]. Evaluating the correlation between VF indexes values and pressure-induced LC displacement, the authors found that while patients with mild glaucoma presented a posterior LC displacement, those with more advanced disease had an anterior LC displacement [4244].…”
Section: Discussionmentioning
confidence: 94%
“…It is of interest that in some of subjects we saw highly localised areas of deformation ( Figure a , upper middle and lower left examples). These results suggest that in addition to the magnitude of displacement, there may be useful information to be gained in differentiating patients that show diffuse compared with more focal deformation in response to IOP elevation . It should be noted that measured deformations could be affected in some way as a result of unknown tracking and registration methods employed by proprietary OCT software, even though software settings for imaging were kept constant.…”
Section: Discussionmentioning
confidence: 96%
“…reported that greater tissue displacement with IOP elevation was associated with older age and African descent. Some studies have linked these changes to functional deficits; for example, greater transient IOP‐induced thinning of the inferotemporal neuroretinal rim is associated with more severe visual field defect in the corresponding sector . Others have sought to assess the effect of IOP lowering on optic nerve structures in glaucomatous eyes .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ‘static’ information about lamina cribrosa morphology and microstructure offered by OCT, another important area of glaucoma research with potential for eventual clinical use is evaluation of dynamic, biomechanical behaviour of the lamina cribrosa, peripapillary sclera and optic nerve head rim tissue. In this scenario, OCT is used to visualise and quantify structural changes of the optic nerve head in response to transient intraocular pressure elevation, which may reveal otherwise hidden susceptibilities to glaucoma . One can imagine that integrating OCT‐A into this kind of approach, perhaps on a swept‐source platform to improve penetration and signal strength, would offer another important dimension.…”
Section: Future Clinical Potential: Oct For Imaging the Lamina Cribromentioning
confidence: 99%